Bibliometric And Literature Review Of Financing Risk In Islamic Banking - Eka Wahyu Hestya Budianto (Jurnal Perbankan Syariah)
This study aims to show the map of research developments about the risk of financing in Islamic banking using a literature review approach. The object of this research is financing risk. Data sources come from searches of national and international journals indexed by Google Scholar, Sinta, and Scopus through the Publish or Perish software. Data analysis techniques include: mapping RIS (research information systems) data files on Mendeley Desktop based on the order of year, author, and publisher; mapping the results of visualization of bibliometric networks and trends in scientific publications using VOSviewer software; and mapping research topics. The results showed that the number of publications had increased significantly every year. Based on the bibliometric mapping, research on financing risk was obtained, which was grouped into 5 clusters and 85 items along with six gap research. Meanwhile, based on the results of a literature review study, eight main themes surround the risk of financing in Islamic banking. This study can be a reference for future research.